The effect of mild Pulsed Electric Field (PEF) conditions on acid tolerance, bile tolerance, growth and protease activity of the Lactobacillus delbrueckii ssp. bulgaricus LB-12. - Najim, Najim Hadi (The Iraqi Journal of Veterinary Medicine, 2011)
Pulsed electric field (PEF) processing involves the application of pulses of voltage for less than one second to fluid products placed between two electrodes. So this study was conducted for the quantitative assessments of mild PEF conditions on acid tolerance, growth, bile tolerance and protease activity of Lactobacillus delbrueckii ssp. bulgaricus LB-12. The control and PEF treated samples were prepared by inoculating 10 ml of freshly thawed culture of Lactobacillus delbrueckii ssp. bulgaricus LB-12 into 990 ml of sterile 0.1% (wt/v) peptone water and treated in a pilot plant PEF system (OSU-4M). The treatments were positive square unipolar pulse width of 3 μs, pulse period of 0.5 second, voltage of 1 kV/cm, delay time of 20 μs and flow rate of 60 ml/min at 40.5°C. The control was passed through the PEF system (60 ml/min) without receiving any pulsed electric field condition. The acid tolerance was determined every 30 minutes for 120 minutes of incubation in acidified MRS broth at pH 2. Growth was determined hourly for 25 hours of incubation at 37°C in MRS broth. The bile tolerance was determined hourly for 16 hours of incubation in MRS-Thio broth . Samples were plated in duplicates using pH modified Lactobacilli MRS agar. The petriplates were incubated anaerobically at 43C for 72 hours. Protease activity was determined by o-phthaldialdehyde (OPA) UV- spectrophotometric assay at 0, 12, 24, 36 and 48 hours of incubation of conducted. inoculated skim milk at 40°C. Three replications were The control. The stationary phase of the bacterium was between hours 10 and 18. Moreover significant experimental design was repeated measurements on complete randomized block, Replications were the blocks. Data were analyzed using Proc Mixed model of Statistical Analysis System (SAS).The viability of the control Lactobacillus delbrueckii ssp. bulgaricus LB-12 was lost after 30 minutes of incubation in acidified MRS broth (pH 2), whereas, the bacterium subjected to mild PEF treatment was acid tolerant until the end of 120 minutes of incubation. Mild PEF significantly improved acid tolerance of Lactobacillus delbrueckii ssp. bulgaricus LB-12. and the growth reached the logarithmic phase an hour earlier than the decrease